ترجيحات ابن يونس من خلال المختصر خليل - بلقرين محمد; خيموج وليد; د/ مايدي عبدالرحمان (جامعة عمار ثليجي الاغواط, 2024)
الملخص : تم في هذا البحث عرض مفهوم الترجيح في مختصر خليل بن إسحاق المالكي للإمام ابن يونس الصقلي حيث يقول مؤلف المختصر وبـ"الترجيح" لابن يونس كذلك" وتمكذلك عرض سيرته ومنهجه ومؤلفاته ثم بعد ذلك بسط لترجيحاته وما انفرد به في المختصر. خلص الباحث فيه إلى إبراز علو كعب هذا العالم التحرير ومكانته العلميةاعتماد ترجيحاته مصدرا من المصادر التي اعتمد عليها العالم الجهبذ المالكي الشيخ خليل بن إسحاق فيتّأليف هذا السفر النفيس المختصر في الفقه المالكي والموسوم بمختصر خليل في الفقه المالكي والذي حظيبالقبول عند اهل العلم وطلبته. Abstract: This research presented the concept of preference in the summary of Khalil bin Ishaq Al-Maliki by Imam IbnYounis Al-Siqilli, where the author of the summary says, “and with ‘preference’ by IbnYounis as well,” and also presented his biography, methodology, and writings, then after that, he expanded on his preferences and what he uniquely included in the summary. The researcher concluded by highlighting the high status of this distinguished scholar and his scientific position, adopting his preferences as a source from the sources that the great Maliki scholar Sheikh Khalil bin Ishaq relied on in composing this precious summary of Maliki jurisprudence, entitled Khalil’s Summary of Maliki Jurisprudence, which was accepted by scholars and students.
دراسة نماذج من المعاملات المالية